2017 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2017
DOI: 10.1109/icassp.2017.7952536
|View full text |Cite
|
Sign up to set email alerts
|

Phonological content impact on wrongful convictions in Forensic Voice Comparison context

Abstract: Forensic Voice Comparison (FVC) is increasingly using the likelihood ratio (LR) in order to indicate whether the evidence supports the prosecution (same-speaker) or defender (different-speakers) hypotheses. Nevertheless, the LR accepts some practical limitations due both to its estimation process itself and to a lack of knowledge about the reliability of this (practical) estimation process. It is particularly true when FVC is considered using Automatic Speaker Recognition (ASR) systems. Indeed, in the LR estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Automatic Speaker Recognition (ASpR) is considered as one of the most appropriate solution [3]. Even if impressive low error rates (≈ 1% [4,5]) were reported in the last years, the forensic scenario is still very challenging for ASpR for several reasons [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Automatic Speaker Recognition (ASpR) is considered as one of the most appropriate solution [3]. Even if impressive low error rates (≈ 1% [4,5]) were reported in the last years, the forensic scenario is still very challenging for ASpR for several reasons [6].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the speaker himself is an important factor [10,6,11]. A speaker could be ill, or under the influence of stress, alcohol or other drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social and linguistic environment of the unknown speaker is unknown by construction (so, for example, an unknown native or second language should be taken into account by the forensic experts). The speakers intrinsic characteristics may have a huge impact on the intraspeaker variability and therefore put into question the validity and reliability of FVC [8,19,20]. Indeed, in [19], we showed that speakers do not behave the same way in response of similar condition changes: some speakers will be quite robust with limited LR variation when some other are showing a huge variation.…”
Section: Introductionmentioning
confidence: 97%
“…And finally, the speaker himself is an important factor [18,8,19,20]. A speaker could be ill, or under the influence of stress, alcohol or other factors.…”
Section: Introductionmentioning
confidence: 99%